Exploring the Value of Service Learning: Students' assessments of Personal, Procedural and Content Learning - David García Romero; Sònia Sànchez Busqués; José Luis Lalueza Sazatornil (Universidad de Navarra, 2018)
Research into Service Learning (S-L) has investigated the value of this pedagogy to construct student learning and foster commitment to social issues. Most research focuses on the positives outcomes of S-L, without considering comparison with other practices. We aim to contribute to this research from a critical point of view by performing a comparative analysis between S-L and other models of practice. Using the Course Value Inventory scale, we compare the assessment of 174 students taking a Bachelor's degree in Psychology, considering their participation in S-L or non-S-L practice. We intent to test if there are differences in the students' assessment between the two models of practice in what concerns to authentic learning. We compare separately the three dimensions of this construct: personal learning, procedural learning and content learning to fi nd or discard the value of S-L in this matter. The results are discussed in relation with previous studies from a cultural-historical approach in order to make sense of the found differences and propose further research.